Smart Power Monitoring System CCTV Menggunakan Internet of Thing - Warta, Joni; Priatna, Wowon; Srisulistiowati, Dwi Budi (TEMATIK, 2023)
The purpose of this research is to design an intelligent monitoring system to monitor CCTV installed on the highway using internet of things (IOT) technology. CCTV monitoring was previously used only for monitoring and recording events from objects caught by CCTV and can be accessed through an application provided by the supplier of the CCTV brand so that it is not difficult to configure according to the needs of the user. In this research designing CCTV smart power monitoring apart from monitoring and recording objects, this smart power system can find out time, address, code, voltage, electric current, total kwh and electricity costs which display variable values ​​that are measurable and can be controlled through an application that can and accessed using the internet and smartphones. The resulting data can be used as a reference..